2022
DOI: 10.3390/su14137601
|View full text |Cite
|
Sign up to set email alerts
|

Development of High-Strength Geopolymer Concrete Incorporating High-Volume Copper Slag and Micro Silica

Abstract: The present work investigates the mechanical and chemical characteristics and durability of high-strength geopolymer concrete (HSGPC) developed using high-volume copper slag and micro silica. The objective of the study was to explore the feasibility of deploying high-volume copper slag as a replacement for river sand in the fabrication of high-strength geopolymer concrete. In total, 11 different trials were cast by varying copper slag up to 100% as a potential alternative for the river sand. The mixture of alk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…A water absorption test for thin brick and stone veneer was carried out following the ASTM standard C67 [38]. This test aims to determine the durability of produced samples in changing weather conditions [42]. The thin brick samples for the water absorption test have length (L) 95 × breadth (B) 90, with two different thicknesses (T) of 13 mm and 27 mm.…”
Section: Test Methodsmentioning
confidence: 99%
“…A water absorption test for thin brick and stone veneer was carried out following the ASTM standard C67 [38]. This test aims to determine the durability of produced samples in changing weather conditions [42]. The thin brick samples for the water absorption test have length (L) 95 × breadth (B) 90, with two different thicknesses (T) of 13 mm and 27 mm.…”
Section: Test Methodsmentioning
confidence: 99%
“…Also, in addition to the above types of aluminosilicate components, metakaolin, microsilica and ground waste from concrete and brick waste are used for the production of geopolymer composites [18][19][20]. The combination of these types of aluminosilicate components with each other in optimal quantities makes it possible to obtain durable composites with high mechanical characteristics [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Arunachelam et al [8] reported that the geopolymer concrete made with 10 molarity raised the concrete's strength by approximately 35% when the molarity of the NaOH solution was increased to 16 M. Additionally, the compressive strength was increased by 53.8% when river sand was replaced with 100% copper slag compared to the control geopolymer concrete made with no copper slag. Te use of high-volume copper slag instead of river sand in the production of high-strength geopolymer concrete was studied by Arunachelam et al [9]. According to the fndings, the optimized geopolymer concrete mix achieved a maximum compressive strength of 79.0 MPa when 2% microsilica was added.…”
Section: Introductionmentioning
confidence: 99%